Pricing Partially Guaranteed Bonds : Valuation of Bonds Benefitting from a World Bank Partial Guarantee - Launay, Vincent (World Bank, Washington, DC, 2016)
The absence of sovereign bond issuances with World Bank guarantee support for almost 15 years and the customized application of the WB guarantee instrument led potential investors in the Ghana bond to ponder the best way to value the instrument. This paper provides guidance on this subject by presenting four ways to assess the value of a World Bank guarantee for debt capital market issues. The methodologies presented are: nominal weighted average yield; rolling nominal weighted average yield; discounted cash flow; and recovery analysis. The paper presents the methodologies by applying them to a fictional bond issuance by the government of Emergistan, a fictional low income country. Background information on the country and bond issuance has been kept to the minimum as the sole purpose of this example is to illustrate the results of each of the methodologies. It should be noted that World Bank guarantees can be structured in a number of ways depending on the issuer’s objectives as well as country and market circumstances. For instance, guarantees could cover interest and/or principal payments of bonds. Coverage could be on a first loss or back-ended basis. Therefore, the most appropriate valuation method would depend on the specific features of the guarantee being considered.